2016
DOI: 10.1016/j.neuro.2016.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Sex-dependent effects of lead and prenatal stress on post-translational histone modifications in frontal cortex and hippocampus in the early postnatal brain

Abstract: Environmental lead (Pb) exposure and prenatal stress (PS) are co-occurring risk factors for impaired cognition and other disorders/diseases in adulthood and target common biological substrates in the brain. Sex-dependent differences characterize the neurochemical and behavioral responses of the brain to Pb and PS and sexually dimorphic histone modifications have been reported to occur in at-risk brain regions (cortex and hippocampus) during development. The present study sought to examine levels and developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 38 publications
3
39
1
Order By: Relevance
“…However, there has been only one genome-wide study detailing sex-specific differences in H3K4me3 levels, which is surprising considering the demonstration of sexually dimorphic gene expression associated with H3K4-methyltransferase and demethylase enzymes in various brain regions. In a study by Schneider et al, in frontal cortex and hippocampus they have demonstrated a sexually dimorphic effect of stress (lead exposure and prenatal stress) on post translational histone modifications (H3K9/14Ac and H3K9Me3) (Schneider et al 2016). They also suggest that, on the hippocampus this effect might be greater in males than in females.…”
Section: Histone Modificationsmentioning
confidence: 99%
“…However, there has been only one genome-wide study detailing sex-specific differences in H3K4me3 levels, which is surprising considering the demonstration of sexually dimorphic gene expression associated with H3K4-methyltransferase and demethylase enzymes in various brain regions. In a study by Schneider et al, in frontal cortex and hippocampus they have demonstrated a sexually dimorphic effect of stress (lead exposure and prenatal stress) on post translational histone modifications (H3K9/14Ac and H3K9Me3) (Schneider et al 2016). They also suggest that, on the hippocampus this effect might be greater in males than in females.…”
Section: Histone Modificationsmentioning
confidence: 99%
“…Both Pb and PS also have effects on the epigenome (Oberlander et al, 2008; Senut et al, 2012; Faulk et al, 2013; Matrisciano et al, 2013) yet little is known about how these effects might be manifested from early development through adulthood. We previously reported differences in levels of histone modifications H3K9/14Ac and H3K9Me3 and the developmental trajectory of changes in these histone levels from day of birth (PND0) to postnatal day 6 (PND6) in hippocampus (HIPP) and frontal cortex (FC) and that these parameters were differentially affected by Pb, PS, and the combination, in a sex and brain-region-dependent manner (Schneider et al, 2016). The current study was performed to extend these findings by examining the extent to which Pb, PS and Pb + PS affects levels of other post-translational histone modifications (PTHMs) H3K9Ac, H3K4Me3 (activating marks) and H3K9Me2 and H3K27Me3 (repressive marks) in FC and HIPP during fetal development (E18), early postnatal life (PND0, PND6) and in adulthood (PND60) in males and females.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these consistent sex differences [38] are both brain region- and time point of measurement-dependent differences in brain epigenetic responses to Pb and PS. For example, offspring of C57Bl6 mouse dams treated from 2 mos prior to breeding through lactation with 0 or 100 ppm Pb drinking solutions combined with either no prenatal restraint stress or PS administered 3x/day for 30 min each time from gestational days 11–19 showed brain region differences as indicated by differing PTHM profiles in FC as compared to HIPP [37]. Each treatment group (0-NS: no Pb, no PS; 0-PS: no Pb, PS; Pb-NS: Pb, no PS; Pb-PS: Pb and PS) showed unique transitions in PTHMs from P0 to P6 and these treatment-related differences varied between the HIPP and FC.…”
Section: Introductionmentioning
confidence: 99%
“…In FC, expression levels of both marks again decreased significantly between PND0 and PND6 in females, but here Pb±PS did influence outcomes: Pb alone reduced expression levels of H3K9/14Ac at PND0 and PS alone reduced levels of H3K9Me3. In male FC, expression levels of both marks also declined between PND0 and PND6, while PS alone significantly increased H3K9/14Ac at PND0 [37]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation